Negative electrode for lithium secondary battery and lithium secondary battery comprising the same

CN122930838APending Publication Date: 2026-10-16SK ON CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202610449000.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2025-04-08
Filing Date
2026-04-07
Publication Date
2026-10-16

AI Technical Summary

Benefits of technology

[0021]A lithium secondary battery according to one embodiment includes a negative electrode for a lithium secondary battery according to any of the above embodiments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122930838A_ABST
    Figure CN122930838A_ABST
Patent Text Reader

Abstract

A negative electrode for a lithium secondary battery includes a negative electrode current collector; and a negative electrode mixture layer on at least one surface of the negative electrode current collector, wherein the negative electrode mixture layer includes a carbon-based active material, and wherein a peak intensity ratio of the negative electrode mixture layer is 1.85 to 3.5 according to the following Formula 1, [Formula 1] Peak intensity ratio = I 2H(100) / I 3R(101) wherein in Formula 1, I 2H(100) is a peak intensity value of a 2H(100) crystal plane in an X-ray diffraction pattern obtained by XRD analysis, I 3R(101) is a peak intensity value of a 3R(101) crystal plane in an X-ray diffraction pattern obtained by XRD analysis.
Need to check novelty before this filing date? Find Prior Art

Description

Cross-references to related applications

[0001] This patent application claims priority and benefit to Korean Patent Application No. 10-2025-0045198, filed on April 8, 2025, the entire disclosure of which is incorporated herein by reference. Technical Field

[0002] The embodiments of the present invention generally relate to an anode for a lithium secondary battery and a lithium secondary battery containing the anode. Background Technology

[0003] Due to active research into electric vehicles (EVs) as an alternative to fossil fuel vehicles such as gasoline and diesel vehicles (one of the main causes of air pollution), lithium-ion batteries with high discharge voltage and output stability are primarily used as power sources for EVs. Accordingly, technologies for manufacturing high-performance lithium-ion batteries are being actively researched and developed. Summary of the Invention

[0004] Some embodiments of the present invention provide a negative electrode for a lithium secondary battery, the lithium secondary battery having excellent charging and discharging characteristics.

[0005] Some embodiments of the present invention provide a negative electrode for a lithium secondary battery having a high energy density.

[0006] Some embodiments of the present invention provide a negative electrode for a lithium secondary battery, the lithium secondary battery having excellent lifespan performance.

[0007] In some embodiments of the invention, the negative electrode for a lithium secondary battery includes a negative electrode current collector; and a negative electrode mixture layer on at least one surface of the negative electrode current collector, wherein the negative electrode mixture layer contains a carbon-based active material, and wherein the peak intensity ratio of the negative electrode mixture layer according to Formula 1 is from 1.85 to 3.5.

[0008] [Formula 1] Peak intensity ratio = I 2H(100) / I 3R(101) .

[0009] In Equation 1, I 2H(100) I represents the peak intensity value of the 2H(100) crystal plane in the X-ray diffraction pattern obtained by XRD analysis. 3R(101) The peak intensity values ​​of the 3R(101) crystal plane in the X-ray diffraction pattern obtained by XRD analysis are given.

[0010] In some embodiments of the present invention, the negative electrode mixture layer may include a first negative electrode mixture layer on the negative electrode current collector and a second negative electrode mixture layer on the first negative electrode mixture layer, wherein the first negative electrode mixture layer may contain a first carbon-based active material and the second negative electrode mixture layer may contain a second carbon-based active material.

[0011] In some embodiments of the present invention, the first carbon-based active material may include at least one of artificial graphite and natural graphite.

[0012] In some embodiments of the present invention, the content of natural graphite in the first negative electrode mixture layer may be less than 60% by weight, based on the total weight of the first negative electrode mixture layer.

[0013] In some embodiments of the present invention, the second carbon-based active material may include artificial graphite.

[0014] In some embodiments of the present invention, the weight percentage of the first carbon-based active material contained in the first negative electrode mixture layer (based on the total weight of the first negative electrode mixture layer) may be equal to or greater than the weight percentage of the second carbon-based active material contained in the second negative electrode mixture layer (based on the total weight of the second negative electrode mixture layer).

[0015] In some embodiments of the present invention, the content of the first carbon-based active material in the first negative electrode mixture layer can be from 94% to 99% by weight.

[0016] In some embodiments of the present invention, the content of the second carbon-based active material contained in the second negative electrode mixture layer may be from 82% to 97% by weight.

[0017] In some embodiments of the present invention, the second negative electrode mixture layer may further contain a silicon-based active material.

[0018] In some embodiments of the present invention, the first negative electrode mixture layer and the second negative electrode mixture layer may each further comprise an adhesive, wherein the weight percentage of the adhesive contained in the first negative electrode mixture layer (based on the total weight of the first negative electrode mixture layer) may be equal to or greater than the weight percentage of the adhesive contained in the second negative electrode mixture layer (based on the total weight of the second negative electrode mixture layer).

[0019] In some embodiments of the present invention, the first negative electrode mixture layer may not contain conductive material, and the second negative electrode mixture layer may contain conductive material.

[0020] In some embodiments of the present invention, the compaction density of the negative electrode for a lithium secondary battery can be less than 1.64 g / cc.

[0021] A lithium secondary battery according to one embodiment includes a negative electrode for a lithium secondary battery according to any of the above embodiments.

[0022] According to one embodiment of the present invention, the charging and discharging characteristics of lithium secondary batteries can be improved.

[0023] According to another embodiment of the present invention, the energy density of lithium secondary batteries can be improved.

[0024] According to another embodiment of the present invention, the cycle life performance of lithium secondary batteries can be improved. Attached Figure Description

[0025] The following describes in detail certain aspects, features, and advantages of embodiments of the present invention with reference to the accompanying drawings.

[0026] Figure 1 This is a cross-sectional schematic diagram of the structure of a negative electrode for a lithium secondary battery according to one embodiment of the present invention.

[0027] Figure 2 This is a graph showing the rapid life performance evaluation results of the lithium secondary batteries of the embodiments and comparative examples.

[0028] Figure 3 This is a graph showing the life performance evaluation results of the lithium secondary batteries of the embodiments and comparative examples at 45°C. Detailed Implementation

[0029] The features of embodiments of the present invention will be described with reference to the accompanying drawings.

[0030] Some embodiments provide a negative electrode 100 for a lithium secondary battery, the negative electrode 100 including a negative electrode current collector 10; and a negative electrode mixture layer 20 on at least one surface of the negative electrode current collector, wherein the negative electrode mixture layer 20 contains a carbon-based active material, and the peak intensity ratio of the negative electrode mixture layer according to Formula 1 is from 1.85 to 3.5.

[0031] [Formula 1] Peak intensity ratio = I 2H(100) / I 3R(101) .

[0032] In Equation 1, I 2H(100) I represents the peak intensity value of the 2H(100) crystal plane in the X-ray diffraction pattern obtained by XRD analysis. 3R(101) The peak intensity values ​​of the 3R(101) crystal plane in the X-ray diffraction pattern obtained by XRD analysis are given.

[0033] Lithium-ion secondary batteries can exhibit different performance characteristics depending on the type of negative electrode active material they contain. Specifically, during the driving process of a lithium-ion secondary battery, carbon-based active materials, such as graphite, may degrade to varying degrees due to structural changes depending on their type. Therefore, this embodiment provides a negative electrode with excellent performance and a lithium-ion secondary battery incorporating such a negative electrode by controlling a specific peak intensity ratio based on XRD analysis of the negative electrode mixture layer 20 containing carbon-based active material. The negative electrode for a lithium-ion secondary battery will be described in more detail below according to this embodiment.

[0034] The negative electrode 100 for a lithium secondary battery includes a negative electrode current collector 10 and a negative electrode mixture layer 20 on at least one surface of the negative electrode current collector. The composition of the negative electrode current collector 10 is not particularly limited. For example, the negative electrode current collector can be a plate or foil made of indium (In), copper (Cu), magnesium (Mg), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), zinc (Zn), aluminum (Al), germanium (Ge), lithium (Li), or alloys thereof. In some embodiments, the negative electrode current collector can be copper foil (Cu-foil).

[0035] There is no particular limitation on the thickness of the negative electrode current collector 10. For example, the thickness of the negative electrode current collector can be in the range of 0.1 μm to 50 μm.

[0036] The negative electrode mixture layer 20 is a layer containing a negative electrode active material, and according to Formula 1, the negative electrode mixture layer 20 may include a carbon-based active material with a peak intensity ratio of 1.85 to 3.5 as the negative electrode active material. Specifically, according to Formula 1, the peak intensity ratio of the carbon-based active material may be 1.9 or more, 2.3 or more, 2.6 or more, and 3.2 or less.

[0037] According to Equation 1, the peak intensity ratio refers to the ratio of the peak intensity value of the 2H(100) crystal plane to the peak intensity value of the 3R(101) crystal plane in the X-ray diffraction (XRD) pattern of the negative electrode mixture layer 20 when XRD analysis is performed using CuKα rays. The peak intensity value can be the peak height value or the integral area value of the peak, and according to one embodiment, I in Equation 1... 2H(100) and I 3R(101) The peak intensity can be calculated as the integral area of ​​the peak. In this paper, peak intensity values ​​and their ratios can be measured and calculated by performing XRD analysis under the following analytical conditions.

[0038] -2θ: 10°~80° -Step size: 0.006565° / step -Time per step: 100 seconds Scan rate = 0.0673° / second The peak intensity ratio according to Equation 1 can be measured by pulverizing the negative electrode mixture layer 20 obtained by peeling it off from the negative electrode current collector 10. In this study, the negative electrode mixture layer 20 can be pulverized to minimize breakage of the negative electrode active material and randomize the orientation of the carbon-based active material. For example, the negative electrode mixture layer 20 can be pulverized using a pulverizing stick, and then a powder form of the negative electrode mixture layer with a particle size of 10 μm to 20 μm can be obtained by particle separation. The peak intensity ratio of the powder form of the negative electrode mixture layer can be measured using the same method described above. In this study, particle size can refer to the length of the longest axis of the particles in the powder form of the negative electrode mixture layer.

[0039] In some implementations, the negative electrode for a lithium secondary battery can have a multilayer structure (see...). Figure 1 Specifically, the negative electrode mixture layer 20 may include a first negative electrode mixture layer 21 on the negative electrode current collector 10 and a second negative electrode mixture layer 22 on the first negative electrode mixture layer. In the negative electrode mixture layer 20, the first negative electrode mixture layer 21 adjacent to the negative electrode current collector 10 may contain a first carbon-based active material, and the second negative electrode mixture layer 22 spaced apart from the negative electrode current collector may contain a second carbon-based active material. The first carbon-based active material and the second carbon-based active material may be different from each other or the same as each other.

[0040] In the above embodiments, for the form (or state) in which the first negative electrode mixture layer 21 and the second negative electrode mixture layer 22 are mixed, the peak intensity ratio of the negative electrode mixture layer 20 can be measured according to Equation 1. Specifically, the negative electrode mixture layer 20 containing the first negative electrode mixture layer 21 and the second negative electrode mixture layer 22 is peeled off from the negative electrode current collector 10 and then pulverized to measure the peak intensity ratio of the powdered negative electrode mixture layer.

[0041] The negative electrode mixture layer 20, comprising the first negative electrode mixture layer 21 and the second negative electrode mixture layer 22, can be pulverized to minimize damage to the negative electrode active material and randomize the orientation of the carbon-based active material. For example, the negative electrode mixture layer 20 can be pulverized using a pulverizing rod, and then a powdered negative electrode mixture layer with a particle size of 10 μm to 20 μm can be obtained through particle separation. The peak intensity ratio of the powdered negative electrode mixture layer can be measured using the same method described above. In this document, particle size can refer to the length of the longest axis of the particles in the powdered negative electrode mixture layer.

[0042] In some embodiments, for the second negative electrode mixture layer 22, the peak intensity ratio of Formula 1 can be equal to or greater than the peak intensity ratio of Formula 1 for the first negative electrode mixture layer 21. Specifically, in the negative electrode 100 for a lithium secondary battery, the peak intensity ratio of the second negative electrode mixture layer 22 located at the top can be higher than the peak intensity ratio of the first negative electrode mixture layer 21 located at the bottom.

[0043] According to one embodiment of the present invention, for a first negative electrode mixture layer and a second negative electrode mixture layer in powder form formed by pulverizing each layer peeled off from the negative electrode current collector 10, the peak intensity ratio of the first negative electrode mixture layer and the second negative electrode mixture layer can be measured respectively, and the pulverization and the method for measuring the peak intensity ratio can be performed as described above.

[0044] According to another embodiment, the peak intensity ratio of each mixture layer can be measured while the first negative electrode mixture layer 21 and the second negative electrode mixture layer 22 are placed on the negative electrode current collector 10. Specifically, the peak intensity ratio of the first negative electrode mixture layer 21 can be measured by XRD analysis after placing the first negative electrode mixture layer on the negative electrode current collector 10; the peak intensity ratio of the second negative electrode mixture layer 22 can be measured by XRD analysis after placing the second negative electrode mixture layer on the negative electrode current collector 10. The XRD analysis method and conditions can be set as described above.

[0045] In some embodiments, according to Formula 1, the peak intensity ratio of the first negative electrode mixture layer 21 can be from 2.5 to 3.3. Specifically, according to Formula 1, the peak intensity ratio of the first negative electrode mixture layer can be from 2.7 or higher to 3.1 or lower.

[0046] In some embodiments, according to Formula 1, the peak intensity ratio of the second negative electrode mixture layer 22 can be from 2.7 to 3.5. Specifically, according to Formula 1, the peak intensity ratio of the second negative electrode mixture layer can be from 2.9 or higher to 3.3 or lower.

[0047] In some embodiments, the ratio of the peak intensity of the (004) crystal plane to the peak intensity of the (110) crystal plane of the first carbon-based active material, as determined by X-ray diffraction (XRD) analysis, is (I (004) / I (110) The ratio of the peak intensity of the (004) crystal plane to the peak intensity of the (110) crystal plane of the second carbon-based active material can be equal to or less than (I). (004) / I (110) ).

[0048] Specifically, the ratio of the peak intensity of the (004) crystal plane to the peak intensity of the (110) crystal plane of the first carbon-based active material, as determined by X-ray diffraction (XRD) analysis (I...(004) / I (110) The value can be in the range of 1 to 10. More specifically, the I of the first carbon-based active material... (004) / I (110) The value can be 1.5 or higher, 2 or higher, or 3 or higher, and can be 8 or lower, 6 or lower, or 4 or lower.

[0049] Specifically, the ratio of the peak intensity of the (004) crystal plane to the peak intensity of the (110) crystal plane of the second carbon-based active material, as determined by X-ray diffraction (XRD) analysis (I... (004) / I (110) The value can be in the range of 2 to 15. More specifically, the I of the second carbon-based active material... (004) / I (110) The value can be 2.5 or higher, 3 or higher, or 4 or higher, and can be 10 or lower, 7 or lower, or 5 or lower.

[0050] The peak intensities of the (004) and (110) crystal planes can be calculated as the integrated area values ​​of the peaks of the (004) and (110) crystal planes in the X-ray diffraction (XRD) pattern when using CuKα rays for XRD analysis. In this paper, the peak intensity values ​​and their ratios can be measured and calculated by performing XRD analysis under the following analytical conditions.

[0051] -2θ: 10°~80° -Step size: 0.006565° / step Time per step: 100 seconds Scan rate = 0.0673° / second In some embodiments, the first carbon-based active material may include at least one of artificial graphite and natural graphite. Specifically, in one embodiment, the first negative electrode mixture layer may include both artificial graphite and natural graphite as the first carbon-based active material. In another embodiment, the first negative electrode mixture layer may include only artificial graphite as the first carbon-based active material.

[0052] In some embodiments, the content of natural graphite in the first negative electrode mixture layer 21 may be less than 60% by weight, based on the total weight of the first negative electrode mixture layer. Specifically, when the first negative electrode mixture layer contains two types (i.e., artificial graphite and natural graphite) as the first carbon-based active material, the content of natural graphite in the first negative electrode mixture layer 21 may be greater than 0% by weight and less than 60% by weight, based on the total weight of the first negative electrode mixture layer 21. Furthermore, when the first negative electrode mixture layer includes only artificial graphite as the first carbon-based active material, the content of natural graphite in the first negative electrode mixture layer may be 0% by weight.

[0053] Based on the total weight of the first negative electrode mixture layer, when the content of natural graphite in the first negative electrode mixture layer 21 is less than 60% by weight, the relatively low-strength natural graphite is distributed relatively less in a portion of the negative electrode mixture layer 20 adjacent to the negative electrode current collector 10, thereby improving the durability of the negative electrode and enhancing the lifespan performance of the lithium secondary battery containing the negative electrode.

[0054] In some embodiments, the second carbon-based active material may include artificial graphite. Specifically, in one embodiment, the second negative electrode mixture layer may consist solely of artificial graphite as the second carbon-based active material.

[0055] The average particle diameter (D50) of artificial graphite is between 10 μm and 20 μm. Specifically, the average particle diameter (D50) of artificial graphite can be greater than 12 μm or greater than 14 μm and less than 18 μm or less than 16 μm.

[0056] The average particle size (D50) of natural graphite is between 6 μm and 16 μm. Specifically, the average particle size (D50) of natural graphite can be greater than 9 μm or greater than 11 μm and less than 15 μm or less than 13 μm.

[0057] There are no particular limitations on the average particle size (D50). For example, the average particle size (D50) can be the particle size value when the accumulated volume fraction reaches 50% by using a particle size analyzer (such as the MT 3000 manufactured by MICROTRAC) based on laser diffraction to accumulate particles in order from smallest to largest.

[0058] The BET specific surface area of ​​artificial graphite can be 0.5 m². 2 / g to 3.5m 2 / g. Specifically, the BET specific surface area of ​​artificial graphite can be 1m². 2 / g or more up to 3m 2 / g or less.

[0059] The BET specific surface area of ​​natural graphite can be 1.5 m². 2 / g to 4.5m 2 / g. Specifically, the BET specific surface area of ​​natural graphite can be 2m². 2 / g or more up to 4m 2 / g or less.

[0060] There are no particular limitations on the methods used to measure BET surface area. For example, BET surface area can be obtained by measuring the amount of nitrogen adsorbed by particles under a nitrogen atmosphere using a gas adsorption analyzer (e.g., Micromeritics TriStarr II) according to ISO-9277.

[0061] The tap density of artificial graphite can range from 0.5 g / cm³ to 3 g / cm³. Specifically, the tap density of artificial graphite can be above 1 g / cm³ or above 1.4 g / cm³, and can be below 2 g / cm³ or below 1.6 g / cm³.

[0062] The tap density of natural graphite can range from 0.5 g / cm³ to 3 g / cm³. Specifically, the tap density of natural graphite can be above 1 g / cm³ or above 1.4 g / cm³, and can be below 2 g / cm³ or below 1.6 g / cm³.

[0063] There are no particular limitations on the method used to measure tapped density. For example, tapped density can be measured as the average of three measurements by compacting a cylinder containing 50.0g of sample 3000 times with a compaction density meter such as Tap Denser KYT-5000 (manufactured by Shih Shin Co., Ltd.), and then reading the scale value.

[0064] In some embodiments, the content (by weight) of the first carbon-based active material contained in the first negative electrode mixture layer can be equal to or greater than the content (by weight) of the second carbon-based active material contained in the second negative electrode mixture layer. Specifically, based on the total weight of the first negative electrode mixture layer 21, the weight percentage of the first carbon-based active material contained in the first negative electrode mixture layer can be equal to or greater than the weight percentage of the second carbon-based active material contained in the second negative electrode mixture layer based on the total weight of the second negative electrode mixture layer 22. In this case, even if the lower first negative electrode mixture layer 21 no longer contains silicon-based active material as the negative electrode active material, the capacity of the lithium secondary battery can be improved.

[0065] In some embodiments, the content of the first carbon-based active material in the first negative electrode mixture layer 21 can be from 94% to 99% by weight. Specifically, the content of the first carbon-based active material in the first negative electrode mixture layer 21 can be from more than 95% by weight to less than 97% by weight.

[0066] In some embodiments, the content of the second carbon-based active material contained in the second negative electrode mixture layer 22 can be from 82% to 97% by weight. Specifically, the content of the second carbon-based active material in the second negative electrode mixture layer 22 can be from more than 83% by weight to less than 93% by weight or less than 86% by weight.

[0067] In some embodiments, based on the entire negative electrode mixture layer 20, the content (by weight) of the first carbon-based active material may be equal to or greater than the content (by weight) of the second carbon-based active material. Specifically, based on the total weight of the entire negative electrode mixture layer 20, the content of the first carbon-based active material may be in the range of 40 wt% to 45 wt%, and the content of the second carbon-based active material may be in the range of 45 wt% to 50 wt%.

[0068] In some embodiments, the second negative electrode mixture layer 22 may further include a silicon-based active material. Specifically, according to one embodiment, in the negative electrode 100 for a lithium secondary battery, the first negative electrode mixture layer 21 only contains the first carbon-based active material as the negative electrode active material, and the second negative electrode mixture layer 22 contains the second carbon-based active material and the silicon-based active material as the negative electrode active materials.

[0069] The silicon-based active material may contain silicon, but is not limited thereto, and may be an active material capable of alloying with lithium (Li). For example, the silicon-based active material may include one or more selected from the group consisting of: silicon (Si), silicon oxide (SiOₓ, 0<x<2), metal-doped silicon oxide (SiOₓ, 0<x<2), carbon-coated silicon oxide (SiOₓ, 0<x<2), silicon-carbon composite (Si-C), and silicon alloy.

[0070] Although the capacity of the silicon-based active material is higher than that of the carbon-based active material, the relatively large volume expansion and contraction during the battery charging and discharging process may cause the negative electrode mixture layer to peel off from the negative electrode current collector. Therefore, when the first negative electrode mixture layer 21 (which is the lower layer adjacent to the negative electrode current collector 10) does not contain the silicon-based active material, and the second negative electrode mixture layer 22 (which is located above the first negative electrode mixture layer 21) contains the silicon-based active material, the high capacity characteristic of the negative electrode can be ensured while suppressing the peeling of the negative electrode.

[0071] In some embodiments, the content of the silicon-based active material in the second negative electrode mixture layer 22 may be 1 wt% to 50 wt%. Specifically, the content of the silicon-based active material in the second negative electrode mixture layer 22 may be at least 5 wt%, or at least 10 wt%, and may not exceed 40 wt%, or not exceed 30 wt% or not exceed 20 wt%.

[0072] In some embodiments, based on the entire negative electrode mixture layer 20, the content of the silicon-based active material may be 1 wt% or more, or 5 wt% or more, and 20 wt% or less, or 10 wt% or less.

[0073] In some embodiments, the first negative electrode mixture layer 21 and the second negative electrode mixture layer 22 may each further comprise an adhesive. The adhesive is not particularly limited and may include, for example, rubber-based adhesives such as styrene-butadiene rubber (SBR), fluoropolymer rubber, ethylene propylene rubber, butadiene rubber, isoprene rubber, or silane-based rubber. According to one embodiment, the adhesive may comprise styrene-butadiene rubber (SBR).

[0074] In some embodiments, the weight percentage of the adhesive contained in the first negative electrode mixture layer (based on the total weight of the first negative electrode mixture layer 21) may be equal to or greater than the weight percentage of the adhesive contained in the second negative electrode mixture layer (based on the total weight of the second negative electrode mixture layer 22).

[0075] Specifically, the adhesive content in the first negative electrode mixture layer can be 0.5% by weight or more, 1% by weight or more, or 2% by weight or more, and can be 5% by weight or less or 3% by weight or less. Furthermore, the adhesive content in the second negative electrode mixture layer can be 0.1% by weight or more, 0.3% by weight or more, or 0.5% by weight or more, and can be 3% by weight or less or 1% by weight or less. In this case, since the adhesive distribution in the first negative electrode mixture layer (which is the lower layer adjacent to the negative electrode current collector 10) is relatively large, the adhesion between the negative electrode current collector and the negative electrode mixture layer can be effectively ensured. That is, excellent adhesion can be achieved.

[0076] In some embodiments, the binder content may be more than 1% by weight or more than 1.3% by weight, and less than 3% by weight or less than 1.7% by weight, based on the entire negative electrode mixture layer 20.

[0077] In some embodiments, the first negative electrode mixture layer 21 and the second negative electrode mixture layer 22 may each contain a thickener. The thickener is not particularly limited. For example, the thickener may include a cellulose-based thickener, such as carboxymethyl cellulose (CMC), hydroxypropyl methylcellulose, methylcellulose, or an alkali metal salt thereof. According to one embodiment, the thickener may include carboxymethyl cellulose (CMC).

[0078] In some embodiments, the thickener contained in each of the first negative electrode mixture layer and the second negative electrode mixture layer may be at least 0.3% by weight, at least 0.5% by weight, or at least 1% by weight, and may be at most 4% by weight or at most 2% by weight.

[0079] In some embodiments, the content of the thickener may be more than 0.7% by weight or more than 1% by weight, and less than 2.5% by weight or less than 1.4% by weight, based on the entire negative electrode mixture layer 20.

[0080] In some embodiments, based on the total weight of the first negative electrode mixture layer 21, the weight percentage of the binder contained in the first negative electrode mixture layer may be equal to or greater than the weight percentage of the thickener contained in the first negative electrode mixture layer; based on the total weight of the second negative electrode mixture layer 22, the weight percentage of the binder contained in the second negative electrode mixture layer may be less than or equal to the weight percentage of the thickener contained in the second negative electrode mixture layer.

[0081] Specifically, the weight ratio of the binder to the thickener contained in the first negative electrode mixture layer 21 can be from 1:1 to 3:1, and the weight ratio of the binder to the thickener contained in the second negative electrode mixture layer 22 can be from 1:1 to 1:3.

[0082] In some embodiments, the content of the binder (by weight) can be equal to or greater than the content of the thickener (by weight) throughout the entire negative electrode mixture layer 20. Specifically, the weight ratio of the binder to the thickener can be from 1:1 to 1.5:1 throughout the entire negative electrode mixture layer 20.

[0083] The negative electrode mixture layer may also contain conductive materials. There are no particular limitations on the type of conductive material. For example, the conductive material may be one or more selected from particulate carbon materials and fibrous carbon materials. Particulate carbon materials may be, for example, carbon black, acetylene black, Ketjen black, etc. of Super-P and Super-C; fibrous carbon materials may be carbon fibers, carbon nanotubes (CNTs), vapor-grown carbon fibers (VGCF), etc.

[0084] In some implementations, the content of conductive material may be more than 0.01% by weight to less than 1% by weight or less than 0.05% by weight, based on the entire negative electrode mixture layer 20.

[0085] The negative electrode mixture layer may also contain a conductive material dispersant. The conductive material dispersant can be a dispersion medium added during the preparation of a pre-dispersion of the conductive material, which is then added to the slurry to prepare the negative electrode mixture layer. For example, the conductive material dispersant can be at least one selected from the group consisting of: aqueous solvents (water, pure water, deionized water, distilled water, hydrochloric acid aqueous solution, sodium hydroxide aqueous solution, etc.), alcohol solvents (ethanol, isopropanol, methanol, acetone, n-propanol, tert-butanol, etc.), and non-aqueous solvents (N-methyl-2-pyrrolidone (NMP), dimethylformamide, dimethylacetamide, N,N-dimethylaminopropylamine, ethylene oxide, tetrahydrofuran, etc.).

[0086] In some embodiments, the content of the conductive material dispersant can be from more than 0.02% by weight to less than 1.5% by weight or less than 0.07% by weight, based on the entire negative electrode mixture layer 20.

[0087] In some embodiments, the first negative electrode mixture layer 21 may not contain a conductive material, while the second negative electrode mixture layer 22 may contain a conductive material. In this case, the first negative electrode mixture layer 21 may also not contain a conductive material dispersant, while the second negative electrode mixture layer 22 may contain a conductive material dispersant.

[0088] As described above, when the first negative electrode mixture layer 21 (which is the lower layer adjacent to the negative electrode current collector 10) does not contain conductive material, and only the second negative electrode mixture layer 22 (which is the upper layer) contains conductive material, conductivity can be improved by adding conductive material, while reducing the total amount of conductive material added, thereby improving economic efficiency.

[0089] In some embodiments, the content of conductive material in the second negative electrode mixture layer may be 0.02% by weight or more, or 0.04% by weight or more, and less than 2% by weight or less than 0.1% by weight. Furthermore, the content of conductive material dispersant in the second negative electrode mixture layer may be 0.04% by weight or more, and less than 3% by weight or less than 1.4% by weight.

[0090] In some embodiments, the ratio of the total weight of silicon-based active material to the total weight of conductive material in the negative electrode mixture layer 20 can be 150 or more. When the ratio of the total weight of silicon-based active material to the total weight of conductive material in the negative electrode mixture layer 20 is 150 or more, the content of silicon-based active material relative to the content of conductive material can be controlled at a high level, thereby improving the performance of the lithium secondary battery.

[0091] Specifically, the ratio of the total weight of silicon-based active material to the total weight of conductive material in the negative electrode mixture layer 20 can be above 170 or above 190, and can be below 500, below 300 or below 210.

[0092] In some embodiments, the total loading weight (LW) of the negative electrode mixture layer 20 can be 5 mg / cm³. 2 Up to 20 mg / cm 2 Specifically, the total loading weight (LW) of the negative electrode mixture layer 20 can be greater than or equal to 10 mg / cm³. 2 And less than or equal to 15 mg / cm 2 .

[0093] In some embodiments, the load weight (LW) ratio between the first negative electrode mixture layer 21 and the second negative electrode mixture layer 22 can be in the range of 30:70 to 70:30. Specifically, the load weight (LW) ratio between the first negative electrode mixture layer 21 and the second negative electrode mixture layer 22 can be in the range of 40:60 to 60:40 or 45:55 to 55:45.

[0094] In some implementations, the rolled density of the negative electrode for a lithium secondary battery can be less than 1.64 g / cm³. Specifically, the rolled density of the negative electrode for a lithium secondary battery can be 1 g / cm³ or more, or 1.5 g / cm³ or more, and can be less than 1.63 g / cm³.

[0095] There are no particular limitations on the manufacturing method of the negative electrode 100 for lithium secondary batteries. For example, the negative electrode 100 for lithium secondary batteries can be prepared by, for example, the following methods: (1) a "two-step coating" process of sequentially coating an upper slurry and a lower slurry; or (2) a "simultaneous coating" process of simultaneously coating an upper slurry and a lower slurry.

[0096] The negative electrode 100 can be prepared by a "two-step coating" process, which includes coating a first solvent and a first negative electrode slurry containing a first carbon-based active material onto a negative electrode current collector 10 by means of, for example, bar coating, casting, or spraying, and drying at about 70°C to about 100°C to form a first negative electrode mixture layer 21. Then, a second negative electrode slurry containing a second carbon-based active material is coated onto the first negative electrode mixture layer 21 by means of, for example, bar coating, casting, or spraying, and drying at about 70°C to about 100°C.

[0097] Solvents may include dimethyl sulfoxide (DMSO), isopropanol, N-methyl-2-pyrrolidone (NMP), acetone, or water. Considering the coating thickness and manufacturing yield of the composition, the amount of solvent used in the composition to form the negative electrode mixture layer should be sufficient to dissolve or disperse the active material, conductive material, and binder, and provide a viscosity that exhibits excellent thickness uniformity when coated to form the negative electrode mixture layer.

[0098] Lithium secondary batteries A lithium secondary battery according to one embodiment includes a negative electrode for a lithium secondary battery according to any of the above embodiments. For example, the lithium secondary battery may include a positive electrode, a negative electrode, and a separator disposed between the positive and negative electrodes. The negative electrode may be a negative electrode for a secondary battery according to any of the above embodiments.

[0099] The positive electrode may include a positive electrode current collector and a positive electrode mixture layer disposed on at least one surface of the positive electrode current collector. The positive electrode current collector may include stainless steel, nickel, aluminum, titanium, or alloys thereof. The positive electrode current collector may also include carbon, nickel, titanium, silver-treated aluminum, or stainless steel. The thickness of the positive electrode current collector may be, for example, from 10 μm to 50 μm, but is not limited thereto.

[0100] The positive electrode mixture layer may include a positive electrode active material. The positive electrode active material may include compounds that enable reversible insertion and extraction of lithium ions.

[0101] According to some embodiments, the positive electrode active material may include lithium nickel metal oxide. The lithium nickel metal oxide may also include at least one of cobalt (Co), manganese (Mn), and aluminum (Al).

[0102] In some embodiments, the positive electrode active material or lithium nickel metal oxide may include a layered structure or a crystal structure represented by the following chemical formula 1.

[0103] Chemical Formula 1 Li x Ni a M b O 2+z In chemical formula 1, x can be in the range of 0.9 to 1.2, a can be in the range of 0.6 to 0.99, b can be in the range of 0.01 to 0.4, and z can be in the range of -0.5 to 0.1. As mentioned above, M can include Co, Mn, and / or Al.

[0104] The chemical structure shown in Formula 1 represents the bonding relationships contained in a layered or crystalline cathode active material, and does not exclude other additional elements. For example, M may include Co and / or Mn, and Co and / or Mn together with Ni can be provided as the main active elements of the cathode active material. Formula 1 is provided to represent the bonding relationships of the main active elements and should be understood to include the introduction and substitution of additional elements.

[0105] In one implementation, to improve the chemical stability of the positive electrode active material or layered / crystal structure, auxiliary elements may be added to the main active element. These auxiliary elements can form bonds by being incorporated into the layered / crystal structure, a situation also understood to be included within the scope of Formula 1.

[0106] The auxiliary element may include at least one of Na, Mg, Ca, Y, Ti, Hf, V, Nb, Ta, Cr, Mo, W, Fe, Cu, Ag, Zn, B, Al, Ga, C, Si, Sn, Sr, Ba, Ra, P, or Zr. The auxiliary element may serve as an auxiliary active element that contributes to the capacity / output activity of the positive electrode active material, such as Al used in conjunction with Co or Mn.

[0107] For example, positive electrode active materials or lithium nickel metal oxides may include the layered or crystalline structures represented by the following chemical formula 1-1.

[0108] Chemical Formula 1-1 Li x Ni a M1 b1 M2 b2 O 2+z In chemical formula 1-1, M1 may contain Co, Mn and / or Al. M2 may contain the aforementioned auxiliary elements. In chemical formula 1-1, x may be in the range of 0.9 to 1.2, a may be in the range of 0.6 to 0.99, b1+b2 may be in the range of 0.01 to 0.4, and z may be in the range of -0.5 to 0.1.

[0109] The positive electrode active material may also include a coating element or a doping element. For example, elements that are substantially the same as or similar to the auxiliary elements mentioned above can be used as coating elements or doping elements. For example, one of the elements mentioned above can be used alone or in combination of two or more of them as coating elements or doping elements.

[0110] The coating or doping elements may be present on the surface of lithium nickel metal oxide particles or penetrate through the surface of lithium nickel metal composite oxide particles to be included in the bonding structure represented by Formula 1 or Formula 1-1.

[0111] The positive electrode active material may include nickel-cobalt-manganese (NCM)-based lithium oxides. In this case, NCM-based lithium oxides with increased nickel content can be used.

[0112] Ni can be provided as a transition metal related to the output and capacity of lithium secondary batteries. Therefore, as mentioned above, using a high-nickel composition in the positive electrode active material can provide a high-capacity positive electrode and a high-capacity lithium secondary battery.

[0113] However, with increasing Ni content, the long-term storage stability and cycle life stability of the cathode or secondary battery may deteriorate, and side reactions with the electrolyte may also increase. However, in some embodiments, the inclusion of Co can maintain conductivity, and the inclusion of manganese can improve cycle life stability and capacity retention.

[0114] The Ni content (e.g., the molar fraction of nickel in the total moles of nickel, cobalt, and manganese) in NCM-based lithium oxides can be 0.6% or more, 0.7% or more, or 0.8% or more. In some embodiments, the Ni content can range from 0.8 to 0.95%, 0.82 to 0.95%, 0.83 to 0.95%, 0.84 to 0.95%, 0.85 to 0.95%, or 0.88 to 0.95%.

[0115] In some embodiments, the positive active material may include a lithium cobalt oxide-based active material, a lithium manganese oxide-based active material, a lithium nickel oxide-based active material, or a lithium iron phosphate (LFP)-based active material (e.g., LiFePO4).

[0116] In some embodiments, the positive active material may include a Mn-rich based active material having a chemical structure or crystal structure represented by Chemical Formula 2, a Li-rich layered oxide (LLO) / over lithiated oxide (OLO)-based active material, and a Co-less based active material.

[0117] Chemical Formula 2 p[Li2MnO3]·(1-p)[LiqJO2] In Chemical Formula 2, 0<p<1, 0.9≤q≤1.2, and J may include at least one element selected from Mn, Ni, Co, Fe, Cr, V, Cu, Zn, Ti, Al, Mg, and B.

[0118] A separator may be disposed between the negative electrode and the positive electrode. The separator may prevent short circuit between the negative electrode and the positive electrode, and allow ions to flow therethrough. According to some embodiments, the thickness of the separator may range from 10 μm to 20 μm, but the embodiments of the present invention are not limited thereto.

[0119] For example, the separator may include a porous polymer membrane or a porous nonwoven fabric. The porous polymer membrane may include a polyolefin-based polymer, such as an ethylene polymer, a propylene polymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methyl acrylate copolymer. The porous nonwoven fabric may include high-melting-point glass fibers, polyethylene terephthalate fibers, and the like. The separator may further include a ceramic material. For example, inorganic particles may be coated on the polymer membrane or dispersed in the polymer membrane to improve heat resistance.

[0120] The separator may have a single-layer structure or a multi-layer structure including the above-described polymer membrane and / or porous nonwoven fabric.

[0121] As described above, the lithium secondary battery has excellent fast charging characteristics, high capacity characteristics, cycle performance, and resistance characteristic, and thus may be very useful as a power source for electric vehicles (EVs).

[0122] Examples and Comparative Examples 1. Fabrication of Negative Electrode and Secondary Battery 1) Anode preparation Two types of artificial graphite (artificial graphite 1 and artificial graphite 2), natural graphite, silicon oxide (SiOx, 0<x<2) as a silicon-based active material, carboxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR) as binders, single-walled carbon nanotubes (SWCNT) as a conductive material, and N-methyl-2-pyrrolidone (NMP) as a conductive material dispersant were prepared.

[0123] In addition, the ratio of the peak intensity of the (004) crystal plane to the peak intensity of the (110) crystal plane (I (004) / I (110) ) of artificial graphite 1, artificial graphite 2 and natural graphite obtained by X-ray diffraction (XRD) analysis is 3.15, 2.73 and 1.81, respectively. In this context, the peak intensities of the (004) crystal plane and the (110) crystal plane can be respectively calculated as the integrated area values of the peaks of the (004) crystal plane and the (110) crystal plane in the X-ray diffraction (XRD) pattern obtained by XRD analysis using CuKα ray, and the XRD analysis conditions are set as follows.

[0124] -2θ: 10° to 80° -Step size: 0.006565° / step Time per step: 100 seconds Scanning rate = 0.0673° / second As shown in Table 1 below, the composition of the negative electrode mixture layer was controlled to be different to prepare negative electrodes for lithium secondary batteries according to Examples and Comparative Examples. Specifically, in Examples 1 to 3 and Comparative Examples 1, 2 and 4, based on solid basis, a first negative electrode slurry and a second negative electrode slurry having the compositions shown in Table 1 below were prepared. Then, the first negative electrode slurry and the second negative electrode slurry were sequentially coated on one surface of a negative electrode current collector (Cu foil), dried and rolled to form a first negative electrode mixture layer and a second negative electrode mixture layer on the current collector, and then subjected to a rolling treatment to prepare a final negative electrode. In this context, the ratio of the loading weight (LW) of the first negative electrode mixture layer to that of the second negative electrode mixture layer is 5:5.

[0125] In addition, in Comparative Example 3, based on solid basis, a negative electrode slurry having the composition shown in Table 1 below was prepared, then coated on one surface of a negative electrode current collector (Cu foil), dried and rolled to form a negative electrode mixture layer having a single-layer structure on the current collector, and then subjected to a rolling treatment to prepare a final negative electrode.

[0126] The total loading weight (LW) of the negative electrode mixture layer and the compaction density of the negative electrode are shown in Table 1 below.

[0127] Table 1

[0128] 2) Secondary battery manufacturing Based on the solids content, a positive electrode slurry was prepared, which contained 98.25% by weight of NCM-based positive electrode active material (Li[Ni)). 0.6 Co 0.1 Mn 0.3 The mixture comprises 0.90 wt% O2, 0.70 wt% binder (polyvinylidene fluoride; PVDF), and 0.15 wt% conductive material (multi-walled carbon nanotubes; MWCNTs) and conductive material dispersant (N-methyl-2-pyrrolidone; NMP). The positive electrode slurry is then uniformly coated onto one surface of the positive electrode current collector (Al foil), dried, and calendered to form a positive electrode mixture layer on one surface of the positive electrode current collector, thereby preparing the positive electrode for lithium secondary batteries.

[0129] A secondary battery cell, assembled by inserting a polyethylene (PE) separator between the positive and negative electrodes prepared as described above, is housed in a pouch for the secondary battery. An electrolyte (prepared by dissolving LiPF6 at a concentration of 1 M in a solvent obtained by mixing ethylene carbonate (EC) and diethyl carbonate (DEC)) is then injected into the pouch for the lithium secondary battery, and the pouch is sealed to manufacture a pouch-type lithium secondary battery. The manufactured pouch-type lithium secondary batteries are used as secondary battery samples for examples and comparative examples.

[0130] 2. Measurement of peak intensity ratio and evaluation of battery performance 1) Peak intensity ratio measurement The negative electrode prepared as described above was subjected to X-ray diffraction (XRD) analysis, and the peak intensity ratio was calculated according to the following formula 1. The results are shown in Table 2.

[0131] [Formula 1] Peak intensity ratio = I 2H(100) / I 3R(101) In Equation 1, I 2H(100) I represents the peak intensity value of the 2H(100) crystal plane in the X-ray diffraction pattern obtained by XRD analysis. 3R(101) The peak intensity values ​​of the 3R(101) crystal plane in the X-ray diffraction pattern obtained by XRD analysis are given.

[0132] Specifically, in Examples 1 to 3 and Comparative Examples 1, 2, and 4, the peak intensity ratio (i.e., measured under the mixed state of the first and second negative electrode mixture layers) of the negative electrode mixture layer, which was obtained by peeling off the negative electrode mixture layer (first negative electrode mixture layer and second negative electrode mixture layer) from the double-layer negative electrode current collector and then pulverizing it, was measured. In this study, after pulverization with a pulverizing rod, a negative electrode mixture layer in powder form with a particle size of 10 μm to 20 μm was obtained through particle separation, where the particle size was measured as the length of the longest axis of the powder form of the negative electrode mixture layer. Subsequently, XRD analysis of the powder form of the negative electrode mixture layer was performed using an XRD instrument (Empyrean manufactured by PANalytical) with CuKα rays as the target. The analytical conditions were set as follows.

[0133] -2θ: 10°~80° -Step size: 0.006565° / step Time per step: 100 seconds Scan rate = 0.0673° / second In addition, for Comparative Example 3 (which is a negative electrode with a single-layer structure), after the negative electrode mixture layer was peeled off from the negative electrode current collector, XRD analysis was performed in the same manner as described above.

[0134] 2) Rapid lifespan performance At 25°C, the secondary battery sample was charged from SOC 10 to 80 (cutoff voltage 4.4V) for 20 minutes, and then discharged to SOC 10 (1.0C CC, cutoff voltage 2.5V). This charge / discharge process was repeated 300 times. Figure 2 The calculated discharge capacity retention rate (expressed as a percentage) relative to the initial discharge capacity at a specific number of cycles is shown. Furthermore, Table 2 shows the measured capacity retention rate at 150 and 300 cycles.

[0135] 3) Life performance at 45℃ The secondary battery samples were subjected to the following charge-discharge cycles at 45°C: the secondary battery samples were charged at 0.33C and discharged at 0.5C within the range of SOC 4% to 98%. Figure 3 The calculated discharge capacity retention rate (expressed as a percentage) relative to the initial discharge capacity at a specific number of cycles is shown. Furthermore, Table 2 shows the measured discharge capacity retention rates for 200, 300, and 400 cycles.

[0136] Table 2

[0137] Refer to Tables 1 and 2 and Figure 2 and Figure 3 In Comparative Examples 1, 3, and 4, the peak intensity ratio of the negative electrode mixture layer was less than 1.85, resulting in poor rapid life performance and 45°C life performance of the battery. Furthermore, it can be seen that in Comparative Example 2, the peak intensity ratio of the negative electrode mixture layer exceeded 3.5, leading to poor rapid life performance and 45°C life performance of the battery.

[0138] On the other hand, in Examples 1 to 3, it can be seen that the peak intensity ratio of the negative electrode mixture layer is 1.85 to 3.5, and the battery's rapid life performance and 45°C life performance are both excellent.

[0139] Only some embodiments have been described. Variations, improvements, and enhancements can be made to the disclosed embodiments and other embodiments based on this invention. Furthermore, embodiments can be combined to form other embodiments.

[0140] Explanation of reference numerals in the attached figures 10: Negative electrode current collector 20: Negative electrode mixture layer 21: First negative electrode mixture layer 22: Second negative electrode mixture layer 100: Anode used in lithium secondary batteries

Claims

1. A negative electrode for a lithium secondary battery, the negative electrode comprising: Negative electrode current collector; as well as A negative electrode mixture layer on at least one surface of the negative electrode current collector. The negative electrode mixture layer comprises a carbon-based active material, and the peak intensity ratio of the negative electrode mixture layer according to Formula 1 is from 1.85 to 3.

5. [Formula 1] Peak intensity ratio = I 2H(100) / I 3R(101) In Equation 1, I 2H(100) I represents the peak intensity value of the 2H(100) crystal plane in the X-ray diffraction pattern obtained by XRD analysis. 3R(101) The peak intensity values ​​of the 3R(101) crystal plane in the X-ray diffraction pattern obtained by XRD analysis are given.

2. The negative electrode for a lithium secondary battery according to claim 1, wherein the negative electrode mixture layer comprises: The first negative electrode mixture layer on the negative electrode current collector; and The second negative electrode mixture layer on the first negative electrode mixture layer. The first negative electrode mixture layer contains a first carbon-based active material, and the second negative electrode mixture layer contains a second carbon-based active material.

3. The negative electrode for a lithium secondary battery according to claim 2, wherein the first carbon-based active material comprises at least one of artificial graphite and natural graphite.

4. The negative electrode for a lithium secondary battery according to claim 2, wherein the content of natural graphite in the first negative electrode mixture layer is less than 60% by weight based on the total weight of the first negative electrode mixture layer.

5. The negative electrode for a lithium secondary battery according to claim 2, wherein the second carbon-based active material comprises artificial graphite.

6. The negative electrode for a lithium secondary battery according to claim 2, wherein the weight percentage of the first carbon-based active material contained in the first negative electrode mixture layer based on the total weight of the first negative electrode mixture layer is equal to or greater than the weight percentage of the second carbon-based active material contained in the second negative electrode mixture layer based on the total weight of the second negative electrode mixture layer.

7. The negative electrode for a lithium secondary battery according to claim 6, wherein the content of the first carbon-based active material in the first negative electrode mixture layer is 94% to 99% by weight.

8. The negative electrode for a lithium secondary battery according to claim 6, wherein the content of the second carbon-based active material contained in the second negative electrode mixture layer is from 82% to 97% by weight.

9. The negative electrode for a lithium secondary battery according to claim 2, wherein the second negative electrode mixture layer further comprises a silicon-based active material.

10. The negative electrode for a lithium secondary battery according to claim 2, wherein the first negative electrode mixture layer and the second negative electrode mixture layer each further comprise an adhesive, wherein the weight percentage of the adhesive contained in the first negative electrode mixture layer based on the total weight of the first negative electrode mixture layer is equal to or greater than the weight percentage of the adhesive contained in the second negative electrode mixture layer based on the total weight of the second negative electrode mixture layer.

11. The negative electrode for a lithium secondary battery according to claim 2, wherein the first negative electrode mixture layer does not contain a conductive material, and the second negative electrode mixture layer further contains a conductive material.

12. The negative electrode for a lithium secondary battery according to claim 1, wherein the compaction density of the negative electrode for the lithium secondary battery is less than 1.64 g / cm³.

13. A lithium secondary battery, the lithium secondary battery comprising the negative electrode for a lithium secondary battery according to claim 1.

Citation Information

Patent Citations

  • Double safety of portable gas burners

    KR1020250045198A